Reducing Intrathecal Baclofen Related Infections: Service Evaluation and Best Practice Guidelines. Issue 7 (12th December 2019) - Balaratnam, Michelle S.; Donnelly, Ann; Padilla, Honey; Simeoni, Sara; Bahadur, Sardar; Keenan, Liz; Lee, Heesook; Farrell, Rachel; Curtis, Carmel; Brownstone, Robert M.; Murphy, Mary; Grieve, Joan; et al.
Abstract : Objectives: Intrathecal baclofen (ITB) pumps are an effective treatment for spasticity; however infection rates have been reported in 3–26% of patients in the literature. The multidisciplinary ITB service has been established at The National Hospital for Neurology and Neurosurgery, UCLH, Queen Square, London for over 20 years. Our study was designed to clarify the rate of infection in our ITB patient cohort and secondly, to formulate and implement best practice guidelines and to determine prospectively, whether they effectively reduced infection rates. Methods: Clinical record review of all patients receiving ITB pre‐intervention; January 2013–May 2015, and following practice changes; June 2016–June 2018. Results: Four of 118 patients receiving ITB during the first time period (3.4%, annual incidence rate of infection 1.4%) developed an ITB‐related infection (three following ITB pump replacement surgery, one after initial implant). Infections were associated with 4.2% of ITB‐related surgical procedures. Three of four pumps required explantation. Following change in practice (pre‐operative chlorhexidine skin wash and intraoperative vancomycin wash of the fibrous pocket of the replacement site), only one of 160 ITB patients developed infection (pump not explanted) in the second time period (0.6%, annual incidence rate 0.3%). The infection rate related to ITB surgical procedures was 1.1%. In cases of ITB pump replacement, the infection rate was reduced to 3.3% from 17.6%. Conclusions: This study suggests that a straightforward change in clinical practice may lower infection rates in patients undergoing ITB therapy.